The predictive effects of digital game addiction on social adjustment and school engagement in secondary school students - Yılmaz Dinç, Safiye (Journal of Dependence, 2023)
Objective: This study was carried out to examine the predictive effect of digital game addiction on social adaptation and school adherence in secondary school students. Method: The research was carried out with the relational survey model, one of the quantitative research methods. The sample group of the research consists of 340 randomly selected secondary school students located in Yenimahalle district of Ankara province. Sociodemographic Information Form, Digital Game Addiction Scale, Social Adjustment Scale and School Adherence Scale were used in this study. The determined data collection tools were created through the Web-based application program and presented to the participants online. Results: In this study, 1.5% (5 people) of the sample were game addicts according to the monothetic form (only game addicts), while those who were game addicts and at risk of game addiction according to the polythetic form (game addicts as well as those at risk for game addiction) constitute 27.4% (93 people) of the sample. While digital game addiction significantly predicted social adaptation and school adherence, there was a positive correlation between absenteeism and digital game addiction. Conclusion: There is a significant relationship between digital game addiction and social adaptation and school adherence. By providing controlled digital game play, social adaptation and school adherence levels can be increased. By enabling students to play digital games in a controlled manner, students’ social adaptation and school engagement levels can be increased.